Execution of service workflows in grid environments. (6th July 2010) - Senna, C.R.; Bittencourt, L.F.; Madeira, E.R.M.
OGSA grids use the SOA concepts bringing new challenges for users and grid developers. This paper presents the grid service testbed (GST), an infrastructure for performance evaluation of grid service compositions in grid environments. The GST receives job submissions through a workflow manager using a workflow composition language, which allows services to be invoked sequentially or in parallel. Experimental results, using an image processing filter, show that the overhead when using a service composition scheme does not prevent the grid from giving fast workflow execution. Additionally, we demonstrate how GST manages the dynamicity of grid environments, especially for opportunistic grids, through the dynamic service instantiation and the automatic reference coordination, to choose the best computational resources without user interference. The GST functionalities choose the best resources in a way to improve the performance, besides showing how the developers may use the GST information to support scheduling decisions.